The Christmas genie - Gutman, Dan.; Santat, Dan (New York : Simon & Schuster Books for Young Readers, 2009)
When a meteorite crashes into a fifth-grade classroom at Lincoln School in Oak Park, Illinois, the genie inside agrees to grant the class a Christmas wish--if they can agree on one within an hour.
610
Keywords: Jinn -- Juvenile fiction; Wishes -- Juvenile fiction; Schools -- Juvenile fiction; Meteorites -- Juvenile fiction; Christmas stories